Баллады Адама Мицкевича в художественной интерпретации Александра Пушкина - Macapura, Walentina (Acta Polono-Ruthenica, 2018)
The main target of research in this article is the ballads by Mickiewicz Czaty (The watch), Trzech Budrysów (The three brothers Budrys) in comparison with the ballads by Pushkin Воевода (The waywode) and Будрыс и его сыновья (Budrys and his sons). In particular, there have been compared the artistic specific features of the mentioned works, the role of opposition, the role of ethnic flavour in their structure, language features, peculiarities of rhythm system and stanzaic prosody, functions of aposiopesis, rhetorical questions and exclamations and etc. When finding out the common and the different between the ballads by Mickiewicz and Pushkin, the author of the article points up the difference between the original and the translation. The type of these differences testifies, that the ballads The waywode and Budrys and his sons mediate between the translation and the original creative work and can be considered an independent interpretation of the ballads by Mickiewicz. It becomes apparent especially well in the text of Pushkin’s ballad The waywode.